Pendapatan Asli Daerah Kota Surabaya Sebelum Dan Sesudah Sistem Pajak Online - Aji Rifqi Rawadani; Fidiana (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This research aims to examine the difference of Original Regional Revenue Surabaya before and after the Online Tax System in the 2015-2017 period. The population in this research are hotel tax, restaurant tax, and parking tax in Surabaya city area in every month at 2015-2017 period which amount to 36 data. The data in this research are secondary data covering the realization and target of hotel tax, restaurant tax, and parking tax during the 2015-2017 period obtained from Surabaya City Financial and Regional Tax Management Board. Hypothesis test using independent t independent test analysis, using SPSS. The results showed that there are differences in the original income of Surabaya city before and after the online tax system in 2015-2017. The achievement of effectiveness level before and after the online system is an increase in hotel tax and parking tax, whereas in restaurant tax the achievement of its effectiveness is stable from 2015-2017. So with the online tax system will provide convenience and provide oversight of taxpayers in reporting the amount of tax, so the potential for tax leakage can be minimized which will automatically give influence in increasing the original income of the city of Surabaya